Private standards in pork value chains: Role, impact and potential for local innovation to improve food safety and enhance smallholder competitiveness - Lapar, Ma. Lucila; Tiongco, Marites M. (2011)
Changing demand for livestock products has motivated transformation in the structure of agrifood systems to efficiently deliver products with the desired attributes. Consumers of food from animal-sources are increasingly concerned about food safety, due to recent food scares from food-borne diseases or zoonoses. In cases where there are weak or nonexistant public standards to regulate food safety compliance along the supply chain for animal-source foods (eg by farmers, traders, processors, retailers) private standards have emerged. Private standards by definition are voluntary, but they may in practice become de facto mandatory standards where compliance is required for entry into certain markets. Using insights from available literature and empirical evidence from case studies on the pig sectors in Vietnam and the Philippines, this paper looks at private standards and the role they play in improving the delivery of safe, good quality, pork. The specific case of contract farming is used to illustrate how this form of market organisation and coordination can facilitate the innovation of processes for upgrading smallholders and enhance their competitiveness in an increasingly consumer demand-driven food system. The main focus of private standards is management of food safety risk along the value chain in order to achieve a higher level of assurance in terms of regulatory compliance, and to capture price premiums and market share of the ‘certified’ product. In most cases, private standards are implemented at the production and processing stage. However, the cost of implementing these standards is considerably high and as such may not be economically viable for small farm businesses. Contract farming is a form of market organisation that acts as a mechanism for establishing and implementing private standards to produce products with the attributes desired by consumers. In the developing country context, suppliers of products (eg pig growers) are required to follow specific process (eg specific types of inputs used, adhering to specific production practices, etc) and performance standards (eg feed-conversion ratio, mortality rates, etc). Non-compliance will result in penalties such as price discounts for pigs. The use of private standards is seen as a potentially effective strategy to jumpstart local innovation for the adoption and adaptation of new norms to enhance food safety and improve product quality.